An Empirical Analysis of Digital Transformation Synchronicity and Transformational Leadership Style in Stimulating Employee Performance: A Study on the Regional State-Owned Capital Market Industry - Arsenio Manuel Boavida; Kuras Purba; Marupa Siregar; Santi Rizki; Owen Depinto Simanjuntak (Jurnal Manajemen Riset Inovasi, 2026)
The accelerated technological disruption in the Industrial Revolution 4.0 era has forced the capital market industry to reorient its operational strategy through digitalization. This study aims to empirically analyze the effect of digital transformation and transformational leadership style on employee performance at PT Mandiri Sekuritas Medan Branch. Employing an explanatory quantitative approach, data were gathered using structured questionnaires from 87 employees selected via probability sampling from a total population of 111 staff. Multiple Linear Regression analyzed through SPSS 26 was utilized. Partial testing reveals that digital transformation significantly enhances employee performance (t = 2.799, p < 0.05). Similarly, transformational leadership style acts as a dominant catalyst, positively and significantly impacting individual performance (t = 3.360, p < 0.05). Simultaneously, both independent variables significantly predict employee execution (F = 14.708, p < 0.000) with a coefficient of determination (R2) of 25.9%. The remaining 74.1% variance is defined by external elements outside this model, such as work motivation, loyalty, and corporate culture. Strategic recommendations emphasize the critical convergence of high-tier digital infrastructure provision (advanced analytics) and visionary leadership development to mitigate employee technostress in regional financial markets.